An Isolated Molecule of Iron(II) Phthalocyanin Exhibits Quintet Ground‐State: A Nexus between Theory and Experiment. Issue 51 (29th August 2018) - Nachtigallová, Dana; Antalík, Andrej; Lo, Rabindranath; Sedlák, Robert; Manna, Debashree; Tuček, Jiří; Ugolotti, Juri; Veis, Libor; Legeza, Örs; Pittner, Jiří; Zbořil, Radek; Hobza, Pavel
Abstract: Iron(II) phthalocyanine (FePc) is an important member of the phthalocyanines family with potential applications in the fields of electrocatalysis, magnetic switching, electrochemical sensing, and phototheranostics. Despite the importance of electronic properties of FePc in these applications, a reliable determination of its ground‐state is still challenging. Here we present combined state of the art computational methods and experimental approaches, that is, Mössbauer spectroscopy and Superconducting Quantum Interference Device (SQUID) magnetic measurements to identify the ground state of FePc. While the nature of the ground state obtained with density functional theory (DFT) depends on the functional, giving mostly the triplet state, multi‐reference complete active space second‐order perturbation theory (CASPT2) and density matrix renormalization group (DMRG) methods assign quintet as the FePc ground‐state in gas‐phase. This has been confirmed by the hyperfine parameters obtained from 57 Fe Mössbauer spectroscopy performed in frozen monochlorobenzene. The use of monochlorobenzene guarantees an isolated nature of the FePc as indicated by a zero Weiss temperature. The results open doors for exploring the ground state of other metal porphyrin molecules and their controlled spin transitions via external stimuli. Abstract : Isolated iron(II) phthalocyanine (FePc) exhibits a quintet ground‐state as obtained using all multi‐reference calculations including DMRG. This was supported by Mössbauer spectroscopy and magnetic measurements of FePc carried out in frozen non‐polar chlorobenzene solvent, which could perfectly simulate the isolated conditioned of FePc.